Reshaping Canadian History Education to Support Reconciliation - Gibson, Lindsay; Case, Roland (Canadian Journal of Education/Revue canadienne de l’éducation, 2019)
Scholars disagree about the implications of the Truth and Reconciliation Commission’s Calls to Action for history educators and curriculum developers. Some scholars contend that responding to these Calls to Action requires rejecting the discipline of history and historical thinking approaches currently being implemented in history and social studies curricula in several Canadian jurisdictions because they are derived from an ethnocentric Western epistemology. In this article, we propose three significant and important changes to Canadian history education in support of reconciliation, some of which are already underway, albeit imperfectly, and each of which can be implemented without radical epistemological restructuring.